2022
DOI: 10.1038/s41419-022-05463-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of the mitochondrial calcium-dependent potassium channel KCa3.1 triggers cell death and reduces tumor growth and metastasis in vivo

Abstract: Ion channels are non-conventional, druggable oncological targets. The intermediate-conductance calcium-dependent potassium channel (KCa3.1) is highly expressed in the plasma membrane and in the inner mitochondrial membrane (mitoKCa3.1) of various cancer cell lines. The role mitoKCa3.1 plays in cancer cells is still undefined. Here we report the synthesis and characterization of two mitochondria-targeted novel derivatives of a high-affinity KCa3.1 antagonist, TRAM-34, which retain the ability to block channel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…In glioblastoma cells, inhibition of the IK Ca channel also results in increased sensitivity to ionizing radiation [ 54 ]. There are indications that the inhibition of mitochondrial potassium channels may be a promising strategy in cancer therapy, as suggested by in vivo studies [ 10 ]. Hence, our observation is consistent with the effects described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In glioblastoma cells, inhibition of the IK Ca channel also results in increased sensitivity to ionizing radiation [ 54 ]. There are indications that the inhibition of mitochondrial potassium channels may be a promising strategy in cancer therapy, as suggested by in vivo studies [ 10 ]. Hence, our observation is consistent with the effects described above.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that the induction of cell death is caused by an increased level of ROS in the mitochondria due to mitochondrial potassium channel blockage. Similarly, inhibition of the intermediate conductance calcium-activated potassium channel (mitoIK Ca ) may affect mitochondrial function in cancer cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some evidence that mtKCa3.1 may be involved in proliferation, it is inconclusive [122] and cannot exclude the off-target effect [117]. Targeting this channel with novel mitochondria-targeting TRAM-34 derivatives reduced tumor growth and metastasis in orthotopic melanoma and pancreatic ductal adenocarcinoma models [123]. In pancreatic ductal adenocarcinoma cell lines, there is evidence that mtKCa3.1 is involved in mitochondrial respiration and proliferation.…”
Section: Nonspecific Effects Of Kca31 Inhibitors Upon Proliferative C...mentioning
confidence: 99%
“…These channels include the intermediate-conductance calcium-dependent potassium channel (K Ca 3.1) expressed in the plasma membrane and inner mitochondrial membrane (mitoK Ca 3.1). In particular, blocking mitoK Ca 3.1 but not K Ca 3.1 with the inhibitor TRAM-34 results in the in vitro death of tumor cells and reduces their metastatic spread in vivo [215]. The role of potassium channels located in the mitochondrial membrane has also been highlighted by the discovery of a new inhibitor of the K 2P 9.1 (TASK-3) channel.…”
Section: Pharmacological Modulation Of Potassium Channels In Cancermentioning
confidence: 99%